Multi‐stressor impacts on fungal diversity and ecosystem functions in streams: natural vs. anthropogenic stress. Issue 3 (1st March 2015) - Tolkkinen, M.; Mykrä, H.; Annala, M.; Markkola, A. M.; Vuori, K. M.; Muotka, T.
Abstract : Biological assemblages are often subjected to multiple stressors emerging from both anthropogenic activities and naturally stressful conditions, and species' responses to simultaneous stressors may differ from those predicted based on the individual effects of each stressor alone. We studied the influence of land‐use disturbance (forest drainage) on fungal decomposer assemblages and leaf decomposition rates in naturally harsh (low pH caused by black‐shale dominated geology) vs. circumneutral streams. We used pyrosequencing to determine fungal richness and assemblage structure. Decomposition rates did not differ between circumneutral and naturally acidic reference sites. However, the effect of forest drainage on microbial decomposition was more pronounced in the naturally acidic streams than in circumneutral streams. Single‐effect responses of fungal assemblages were mainly related to geology. Community similarity was significantly higher in the naturally acidic disturbed sites than in corresponding reference sites, suggesting that land‐use disturbance simplifies fungal assemblages in naturally stressful conditions. Naturally acidic streams supported distinct fungal assemblages with many OTUs (operational taxonomic unit) unique to these streams. Our results indicate that fungal assemblages in streams are sensitive to both structural and functional impairment in response to multiple stressors. Anthropogenic degradation of naturally acidic streams may decrease regional fungal diversity and impair ecosystem functions, and these globally occurring environments therefore deserve special attention in conservation planning.